Mulher e trabalho: relações de gênero na corporação da Polícia Militar do Espírito Santo (1983-1988) - Cruz, Vagner de Oliveira (2014)
This thesis intend to describe the rejection suffered by women when they are incorporated to the military police of Espírito Santo – PMES, between 1983 and 1988. Rejection that is consequence of social and historical construction of gender relations, formed while the ideal standards of behavior were ordered throughout history, under the tutelage of patriarchal ideology model, which granted to the male gender the predominance of political, social and economical relations. PMES, as study area for considerations proposed on this research, was chosen by its deeply sexist characteristics meanwhile it is a social environment and the opportunity of direct contact with the firsts women that were incorporated at police activities in PMES. When using extensive bibliography related to the theme of gender studies and conducting semi-structured interviews with a fraction of these women from PMES as a source of observations for considerations, it was observed the men rejection to women participating at police activities which, in summary expresses the dynamic relation of power between female and male gender.